Mathematics
Zstricker
16

let f(x)=-2x-7 and g(x)=-4x+3 . Find (f * g)(-5)

+1
(2) Answers
Nunia1567

[latex]f(x)=-2x-7;\ D_f:x\in\mathbb{R}\\\\g(x)=-4x+3;\ D_g:x\in\mathbb{R}\\\\therefore\\\\(f\cdot g)(x)=f(x)\cdot g(x)[/latex] [latex](f\cdot g)(-5)=f(-5)\cdot g(-5)\\\\f(-5)=-2(-5)-7=10-7=3\\\\g(-5)=-4(-5)+3=20+3=23\\\\\boxed{(f\cdot g)(-5)=f(-5)\cdot g(-5)=3\cdot23=69}[/latex]

kingavisingh

[latex](f\cdot g)(x)=f(x)\cdot g(x)\\\\ (f\cdot g)(x)=(-2x-7)(-4x+3)\\ (f\cdot g)(x)=8x^2-6x+28x-21\\ (f\cdot g)(x)=8x^2+22x-21\\\\ (f\cdot g)(-5)=8\cdot(-5)^2+22\cdot(-5)-21\\ (f\cdot g)(-5)=8\cdot25-110-21\\ (f\cdot g)(-5)=200-131\\ (f\cdot g)(-5)=69 [/latex]

Add answer